Total Quality Management System: A Feasibility Study for Application in Cooperative Administration of Khorasan-e- Razavi Province - M Kazemi; A Bagheri (تعاون و کشاورزی, 2009)
The research, introducing the basics of the Total Quality Management System (TQM), proceeds to study the feasibility of its application in the Cooperative Administration of Khorasan-e-Razavi Province in 2007. Being of a survey type, it uses questionnaire as data-collection instrument which comprises five-choice Likert Scale. The statistical population includes all senior and middle-level managers, experts and employees of the Cooperative Administration out of whom Random Stratified Sample of 31 persons was taken. T- Student test was employed to compare mean figures with the total mean in view of the scale being an interval one. Findings show that senior and middle-level managers, unlike employees, do not strongly approve of TQM system. Also, not many experts familiar with TQM are available. All the three groups included in the sample, have shown a reluctant stance towards problem-solving through group-building and collective action or Team-work. The managers not taken into consideration the  motivational mechanisms to encourage participation by the employees;  and lastly to encourage participation by the employees, no significant financial support has been devoted to setting up TQM